Variation in quality of caribou and reindeer forage plants associated with season, plant part, and phenology - Klein, David R. (Rangifer, 1990)
Plant parts used as forage by caribou and reindeer (Rangifer tarandus) have been collected in conjunction with studies of foraging dynamics, nutrition, growth, and population ecology of this arctic ungulate over the course of several years in Alaska and other circumpolar areas. These samples were subjected to proximal analyses for percent nitrogen, phosphorus, sodium, carbohydrate, cell wall (NDF), acid detergent fiber (ADF), lignin, cellulose, and residual ash, and treated to determine in vitro and nylon bag dry matter digestibility (DMD). Among winter vascular plant forage only carbohydrates showed a positive correlation with digestibility, wheras in summer nitrogen, phosphorus, and in some cases sodium, also are positively correlated with digestibility. Forage from shrubs and forbs in early summer had higher nitrogen and carbohydrate levels than later in the season, wheras graminoids show an increase in these levels during the first few weeks of growth. Floral parts during anthesis showed higher nitrogen, phosphorus, and carbohydrate levels and higher digestibility than corresponding leaf material. The annual dietary cycle is the product of adjustment of the physiological cycle to seasonal fluctuation in forage quality and quantity.